Esensi Dakwah di Era Digital dalam Menjawab Problematika Umat - Chudzifah, Ibnu; Muhyiddin, Muh; Hikmah, Afroh Nailil (Tasamuh: Jurnal Studi Islam, 2021)
The Islamic da’wah in the millennial era is now faced with various complex problems. Conditions like this become a motivation and challenge for a da’i (preacher) so that they must have various competencies in dealing with the realities of the times. A reliable preacher is needed who is able to master various kinds of objectivity (disambiguation), both material and formal so that his preaching is pragmatic in dealing with various kinds of problems of the people. Preaching in the millennial era is considered easier than in the past. The problem is that the Islamic sites they visit on the first page are sites affiliated with Wahhabi, Shia, Liberal, and other sects. The contents sometimes even spread slander, hatred, lies, blame fellow Muslims, pit organizations that believe in ahlussunnah waljama’ah against the Shia, and they openly rebel against the legitimate government. Worse yet, Sunni clerics who believe in ahlussunnah waljama’ah such as Sheikh Ramadlan al-Buti were killed because they were slandered as Shi’ites, Sheikh Hassan Saifuddin was sadly beheaded, Sheikh Ahmad Hassoun (Grand Mufti of Syria) was slandered that his fatwa had caused hundreds of thousands of Muslims. Syria’s Sunnis were massacred and millions of people were expelled from their country, and many more. As a result, the da’wah orientation, which originally taught politeness, has become a field for spreading slander and berating.